The Validity of the WHO-5 as an Early Screening for Apathy in an Elderly Population. (6th September 2012) - Lucas-Carrasco, Ramona; Allerup, Peter; Bech, Per
Abstract : Aim . The objective of our study has been to evaluate the WHO-5 as a new early screening instrument for apathy in a group of elderly persons. Methods . The WHO-5 was compared to the Geriatric Depression Scale (GDS-15). The GDS contains five items measuring well-being and ten items measuring depression. The internal validity of the WHO-5 (total score being a sufficient statistic) was evaluated with both parametric and nonparametric item response theory models. The external validity of the WHO-5 and the GDS was evaluated by ROC using depression as index of validity. Results . The item response theory analyses confirmed that the total score of the WHO-5 is a sufficient statistic. The ROC analysis shows an adequate sensitivity (61%) and specificity (84%). The GDS15 and its two subscales obtained low sensitivity (25–42%), but high specificity (90–98%). Conclusion . The WHO-5 was found both internally and externally valid when considering decreased positive well-being to be an early indication of apathy reflecting that the wind has begun to be taken out of the "motivation sail."